Divergent Discourse in Disproportionality Research: A Response to Kauffman and Anastasiou (2019). (September 2019) - Whitford, Denise K.; Carrero, Kelly M.
This article is in response to Kauffman and Anastasiou, wherein the authors initiate discussion regarding the cultural politics within special education identification and placement, particularly surrounding the issue of disproportionality. In this article, we identified four points of discussion regarding societal implications of disproportionality; the roles of (a) divergent ideologies; (b) access and advantage; (c) adult, adolescent, and child behavior; and (d) methodology in the debate on disproportionality in special education identification and placement. Furthermore, we highlight the problems with focusing too heavily on either one of these roles, without proposing viable prevention and intervention efforts to eliminate discriminatory identification and placement in the future. We encourage further discourse in the field that will lead to sound policy and improved practices within and for schools.